CD44: From diagnosis to therapy in the journey of oral cancer - Selvaraj Jayaraman; Vishnu Priya Veeraraghavan (Oral Oncology Reports)
Highlights: • Advancements in OSCC treatment have not reduced mortality due to challenges in early diagnosis, highlighting the need for prognostic biomarkers. • CSCs in OSCC fuel chemo-radio-resistance, making their targeting crucial. • CD44, a CSC biomarker, drives cancer progression and resistance. • Elevated CD44 predicts poor outcomes in various cancers. • Studying CD44's role in OSCC is vital for validating its potential as a prognostic marker and therapeutic target.